Teachers’ Use of Motivational Strategies in the EFL Classroom: A Study of Hungarian High Schools - Bochra Kouraichi; Márta Lesznyák (Anglica. An International Journal of English Studies)
The present study investigates English as a Foreign Language (EFL) teachers’ use of motivational strategies (MS) in Hungarian high schools. It also seeks to identify whether students recognize these strategies. Keller’s (2010) motivational model was employed through the instructional materials motivational survey (IMMS) questionnaire that was translated into Hungarian. A population of 117 Hungarian high school students from grades 9 to 12 filled out questionnaires on their teachers’ use of MS, and 62 high school teachers completed the same questionnaire to report their MS. Classroom observa- tions were also conducted following the Motivational Orientation of Language Teaching (MOLT) scheme proposed by Guilloteaux and Dörnyei (2008). For each grade, face-to-face and online classes were observed. Quantitative and qualitative methods were used to process the data. The results show that teachers’ mean scores for all the ARCS categories were higher than those of students, with significant differences between students’ and teachers’ views on attention and relevance. Teachers reported using satisfaction-generating strategies most often, while the observation results indicated that the most frequently used strategy was attention. Students’ grades had no correlation with students’ perception of the use of MS, which might be due to the homogeneity of the sample selected.